Between Spin and Post-Truth in Politics : The Development of Political Communication and Media Strategy - Veselá, Zuzana (2018)
Mendacity in democratic political campaigns flourishes in highly polarised, personality driven political environment where focus lies on message as opposed to detailed policy. The recent technological advancements which provided disruptions to the traditional media model and allowed politicians to communicate directly with voters through social media further facilitated the ease with which deceitful political message spread without being challenged. This study demonstrates how in such environment mendacity can become a rationally employed tool in a campaign strategy. It provides a comprehensive review of what these mendacity-prone conditions are and how they facilitate the successful use of mendacity. Through comparison of D. Trump´s 2016 presidential campaign and Leave´s official Brexit Campaign this study synthesises an efficient mendacity based communication and media strategy. Its aim is to raise awareness of these practices as they can be corrosive to democracy.